2010
DOI: 10.1073/pnas.0912181107
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of bioencapsulated coagulation factor IX prevents inhibitor formation and fatal anaphylaxis in hemophilia B mice

Abstract: To address complications of pathogenic antibody or life-threatening anaphylactic reactions in protein replacement therapy for patients with hemophilia or other inherited protein deficiencies, we have developed a prophylactic protocol using a murine hemophilia B model. Oral delivery of coagulation factor IX fused with cholera toxin β-subunit (with or without a furin cleavage site; CTB-FFIX or CTB-FIX), expressed in chloroplasts (up to 3.8% soluble protein or 0.4 mg/g leaf tissue), bioencapsulated in plant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
208
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(222 citation statements)
references
References 42 publications
11
208
2
1
Order By: Relevance
“…17,18 Oral delivery of transplastomic plant cells has been effective in prevention of insulitis in nonobese diabetic mice and of inhibitor formation in mice with hemophilia B. 19,20 For FIX inhibitors, immune tolerance induction is often not sustainable because of anaphylactic reactions and the development of nephrotic syndrome. In mice with hemophilia B, we demonstrated that repeated oral delivery of bioencapsulated FIX prevented inhibitor formation and fatal anaphylaxis in subsequent replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Oral delivery of transplastomic plant cells has been effective in prevention of insulitis in nonobese diabetic mice and of inhibitor formation in mice with hemophilia B. 19,20 For FIX inhibitors, immune tolerance induction is often not sustainable because of anaphylactic reactions and the development of nephrotic syndrome. In mice with hemophilia B, we demonstrated that repeated oral delivery of bioencapsulated FIX prevented inhibitor formation and fatal anaphylaxis in subsequent replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, transgenes inserted into chloroplast genomes are expressed at high levels, up to 70% of total leaf protein (De Cosa et al, 2001;Ruhlman et al, 2010). A wide range of proteins, from very small antimicrobial peptides (Lee et al, 2011) or hormones (Boyhan and Daniell, 2011;Kwon et al, 2013) to very large proteins encoded by bacterial, viral, fungal, animal, and human genes, have been expressed successfully in plant chloroplasts (DeGray et al, 2001;Daniell et al, 2009;Verma et al, 2010;Shenoy et al, 2014;Sherman et al, 2014;Shil et al, 2014). Most importantly, expressed proteins are highly stable when lyophilized plant cells are stored at ambient temperature (Kwon et al, 2013;Lakshmi et al, 2013;Kohli et al, 2014;Jin and Daniell, 2015).…”
mentioning
confidence: 99%
“…In 2010, they showed that oral delivery of factor IX expressed in chloroplasts in this way led to almost un detectable inhibitor levels in mice, and no sign of anaphylactic shock 1 . "The mice are healthy, they show no allergic responses and they don't form the inhibitors, " Herzog says.…”
Section: An Act Of Tolerancementioning
confidence: 99%
“…The researchers behind the bio engineered lettuce have shown that inhibitor formation and severe allergic reactions can be prevented in mice by feeding the animals with a product based on these plants 1,2 . If the strategy also works in Anita and her kennel mates -and ultimately in humans -it could form the basis of the first product to protect against the immune responses associated with haemophilia treatment.…”
mentioning
confidence: 99%